2017
DOI: 10.18632/oncotarget.18568
|View full text |Cite
|
Sign up to set email alerts
|

A three gene immunohistochemical panel serves as an adjunct to clinical staging of patients with head and neck cancer

Abstract: BackgroundCurrent management of head and neck squamous cell carcinoma (HNSCC) depends on tumor staging. Despite refinements in clinical staging algorithms, outcomes remain unchanged for the last two decades. In this study, we set out to identify a small, clinically applicable molecular panel to aid prognostication of patients with HNSCC.Materials and MethodsData from The Cancer Genome Atlas (TCGA) was used to derive copy number aberrations and expression changes to identify putative prognostic genes. To accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
(27 reference statements)
0
8
1
Order By: Relevance
“…PSA had positive results in 97.4% of prostate tumors. However, a remarkable point in these studies was that HMWK was positive in 91.4% of bladder tumors, which was much higher than in other studies, including our studies (55.6%) (31).…”
Section: Discussioncontrasting
confidence: 76%
“…PSA had positive results in 97.4% of prostate tumors. However, a remarkable point in these studies was that HMWK was positive in 91.4% of bladder tumors, which was much higher than in other studies, including our studies (55.6%) (31).…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, six-gene expression signatures can be used as independent prognostic markers in survival prediction of patients with breast cancer (11). Using TCGA database, Ong et al successfully identified a powerful biomarker panel for predicting the prognosis progression of patients with head and neck cancer (12). Therefore, by analyzing these big data, researchers can perform prospective clinical trials and evaluate the impact of candidate genes on breast cancer (13).…”
mentioning
confidence: 99%
“…Several groups have demonstrated different approaches to the identification and validation of prognostic factors in HNSCC, largely based on analyses of the primary tumor tissue itself. These include using single gene expression such as mRNA‐based signatures, miRNA expression, single protein biomarkers, or complex multiprotein signatures . Few studies have focused on plasma‐based biomarkers as prognostic factors in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…These include using single gene expression such as mRNA-based signatures, miRNA expression, single protein biomarkers, or complex multiprotein signatures. [21][22][23][24][25] Few studies have focused on plasma-based biomarkers as prognostic factors in HNSCC. Le et al 26 found that serum Osteopontin levels correlated with tumor hypoxia, suggesting that this protein could be used to identify patients at high risk for tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%